RELATIONSHIP ANALYSIS OF THE REOLOGICAL PROPERTIES OF VISCOELASTICITY AND LOCATION / ASBUTON TYPE - SUTRISNI (NIM: 26916005), SRI
Asbuton has unique characteristics in which from mining results in one area has different rheological properties from other regions. The area where the asbuton is mined later in this study is called asbuton type name. Further research needs to be done to be able to map the rheological properties of asbuton so that it can be optimized in its use. The test was carried out to see the rheological properties of asbuton full extraction with empirical tests to obtain asphalt properties and mechanistic tests using Dynamic Shear Rheometer (DSR) to get the value of complex shear modulus and phase angle. The asbuton (Sbit) stiffness modulus value was obtained using the Van der Poel Nomogram and the calculation results using the value of complex shear modulus DSR test results. The modulus value of the asphalt mixture (Smix) was calculated using the Nottingham method. Based on the rheological properties of each type of asbuton can be estimated value of Modulus of asbuton stiffness (Sbit) and modulus of asphalt mixture (Smix) which are influenced by temperature, loading time and type of asbuton. The Sbit value from the Van Der Poel nomogram is greater than the Sbit DSR test results. But there is a similarity in the tendency between the two, the higher the temperature, the modulus value of the asbuton stiffness decreases. Asbuton Lawele has the best workability and durability to be applied in asphalt mixture and has the most flexible properties among the three Asbuton types. Asbuton kabungka has viscous tendencies, its rheological properties are between Asbuton Lawele and Asbuton Winto. Asbuton Winto has the most viscous rheological properties but has the greatest resistance to rutting and fatigue among the three types of asbuton. Asbuton Winto also has the largest PG value so it can withstand heavier loads and is suitable for areas with high temperatures. Lawele Asbuton is thought to be suitable as a mixture of Laston, Rollled Asphalt + chipping, SMA and Porous Asphalt. Asbuton Kabungka is suitable as a mixture of Laston, Rollled Asphalt + Chipping, SMA and Base. Asbuton Winto is estimated to be suitable as a Base mixture.